Functional and genetic characteristics of Chlorantraniliprole resistance in the diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae) - Kang, Won Jin; Koo, Hyun‐Na; Jeong, Dae‐Hun; Kim, Hyun Kyung; Kim, Juil; Kim, Gil‐Hah (Entomological research, 2017)
The diamondback moth ( Plutella xylostella ) is a globally distributed and important economic pest, and it has developed resistance to all conventional insecticide classes used in the field. Chlorantraniliprole is a new chemical class of insecticide that acts as a conformation‐sensitive activator of the insect ryanodine receptor (RyR). In the present study, a field strain (16.3‐fold resistance to chlorantraniliprole) was collected in Korea and lab‐selected with chlorantraniliprole for more than one year. The resulting strain presented 2,157‐fold resistance to chlorantraniliprole. A point mutation (G4946E) in the RyR gene was observed at a high frequency in the resistant strain. Enzyme assays indicated that glutathione S‐transferase (GST) and P450 activity in the resistant strain were 2.4‐ and 1.96‐times higher than that of the susceptible strain, respectively. The expression of the RyR , GST (sigma, omega, and zeta) and CYP321E1 gene was higher in the resistant strain than in the susceptible strain. The F 1 progeny resulting from reciprocal crosses did not reveal maternal effects or a diamide‐susceptible phenotype, which suggests an autosomal nearly recessive mode of inheritance. In addition, we surveyed the susceptibility to 13 insecticides (3 diamides, 2 synthetic pyrethroids, 2 spinosyns, 1 organophosphate, 1 oxadiazine, 1 avermectin, and 3 others) in the chlorantraniliprole‐resistant strain. The resistant strain exhibited high cross‐resistance to flubendiamide (5,910 fold) and showed no cross‐resistance to spinetoram, spinosad, indoxacarb, and metaflumizone. These results can serve as an important basis for guiding the use of insecticides in the field.